Contextual-Based Physics Learning Through Experimental Method to Increase Learning Outcomes in Thermodynamics Material - Amalia Hanifah; Elok Sudibyo; Munasir; Mohammad Budiyanto (Indonesia Approach Education, 2023)
One of the important benefits of implementing meaningful learning for students is improving better learning outcomes. But in general the ability to manage meaningful learning is still relatively low. This study aimed to describe the effectiveness of contextual-based physics learning through experimental method to increase learning outcomes in thermodynamics material. The effectiveness of contextual-based physics learning through experimental method was described based on the data of increasing students’ learning outcomes. This research employed an one-group pretest-posttest pre-experimental design. The results showed that the contextual-based physics learning through experimental method was able to increase learning outcomes of science education students in thermodynamics material with N-gain of 0.69 in medium category increase. Statistical Wilcoxon test also informed that the learning model can significantly improve learning outcomes of science education students in thermodynamics material. Based on the increase of learning outcomes, it can be concluded the contextual-based physics learning through experimental method was effective.